2001
DOI: 10.1105/tpc.13.1.207
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast Ribosomal Protein S7 of Chlamydomonas Binds to Chloroplast mRNA Leader Sequences and May Be Involved in Translation Initiation

Abstract: Certain mutations isolated in the 5 untranslated region (5 UTR) of the chloroplast rps7 gene in Chlamydomonas reduce expression of reporter genes. Second site suppressors in this 5 UTR sequence restore reporter expression. 5 UTR sequences with the original mutations fail to bind a 20-kD protein, one of five proteins that bind to leaders of several chloroplast genes. However, 5 UTRs from suppressed mutants restore binding to this protein but do not bind a 47-kD protein present on the wild type and the original … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Reduced rps7 expression is also likely related to lower growth rates, although this has not been rigorously examined in phytoplankton [53]. Our results suggest that E. huxleyi cells grown under high CO 2 undergo a reduction in translation initiation in some instances [54]. The non-differential expression of histone H2B under different CO 2 conditions may be explained by indications that this protein is involved in processes other than nucleosome packaging since our identification the identified H2B from the E. huxleyi genome (protein ID 96192) also contained a 50S ribosome-binding GTPase (Pfam: CL0023) and a peptidase domain (Pfam: CL0012).…”
Section: Discussionmentioning
confidence: 81%
“…Reduced rps7 expression is also likely related to lower growth rates, although this has not been rigorously examined in phytoplankton [53]. Our results suggest that E. huxleyi cells grown under high CO 2 undergo a reduction in translation initiation in some instances [54]. The non-differential expression of histone H2B under different CO 2 conditions may be explained by indications that this protein is involved in processes other than nucleosome packaging since our identification the identified H2B from the E. huxleyi genome (protein ID 96192) also contained a 50S ribosome-binding GTPase (Pfam: CL0023) and a peptidase domain (Pfam: CL0012).…”
Section: Discussionmentioning
confidence: 81%
“…In a previous study [29], rpl23 was reported to be essential for plants and loss of rpl36 result in severe morphological aberrations, low translational efficiency, poor photoautotrophic growth [29]. As an rRNA binding protein, rps7 plays a role in the regulation of chloroplast translation [30]. However, the experimental research on the specific function of rps7 is limited at present.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that compromised ribosomes may be responsible for the MSC16 phenotype; however, proteomic analysis did not show significant differences in protein production between MSC16 and wild-type B (Del Valle-Echevarria et al 2015). It is possible that translation of certain mitochondrial transcripts is dependent on the RPS7 protein (Fargo et al 2001) and results in the MSC phenotype (Del Valle-Echevarria et al 2015). …”
Section: Discussionmentioning
confidence: 99%